2020
DOI: 10.1111/ped.14265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prostheses on children with congenital upper limb deficiencies

Abstract: Background: Individual weaknesses in motor skills are a characteristic of children with congenital upper limb deficiencies. These weaknesses increase with age. In Japan, however, prosthetic prescription and subsequent rehabilitation approaches for children with upper limb deficiencies are insufficient and often delayed. This study aimed to elucidate whether rehabilitation approaches, including prostheses prescription and occupational therapy, improve these children's adaptive behaviors, especially their motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…These problems worsen with the age of the child [ 16 ]. Appropriate therapy, combined with the use of appropriate and adapted prosthetic equipment, allows problems with incorrect motor skills and motor development of a young person to be alleviated [ 17 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These problems worsen with the age of the child [ 16 ]. Appropriate therapy, combined with the use of appropriate and adapted prosthetic equipment, allows problems with incorrect motor skills and motor development of a young person to be alleviated [ 17 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been reported that the prescription of prostheses and occupational therapy ameliorates children's motor skill weaknesses. 9) In normal practice, the first prosthesis should be prescribed for children with upper limb deficiencies at approximately 6-8 months of age. This is the age at which children without disabilities begin to sit independently with their hands resting on the floor and subsequently without hand support so as to explore and manipulate objects using their hands.…”
Section: Case Reportmentioning
confidence: 99%
“…Children with unilateral transcarpal or transradial upper limb deficiencies who lack adequate experience with prosthetic intervention display weakness in motor skills in the Vineland Adaptive Behavior Scales, Second Edition (Vineland-II) [ 8 , 9 ], a standardized scale of adaptive behavior [ 10 ]. Although motor skill weakness increases with age, it can be improved through rehabilitation approaches, including occupational and prosthetic therapies [ 11 ]. However, the characteristics of intellectual ability and cognitive functioning and the effect of prostheses or rehabilitation approaches on the intellectual development of these children are unknown.…”
Section: Introductionmentioning
confidence: 99%